An N‐Heterocyclic Silylene‐Stabilized Digermanium(0) Complex1. (29th September 2014) - Shan, Yu‐Liang; Yim, Wai‐Leung; So, Cheuk‐Wai
Abstract The synthesis of an N‐heterocyclic silylene‐stabilized digermanium(0) complex is described. The reaction of the amidinate‐stabilized silicon(II) amide [LSiN(SiMe3)2] (1; L=PhC(NtBu)2) with GeCl2⋅dioxane in toluene afforded the SiII–GeII adduct [L{(Me3Si)2N}Si→GeCl2] (2). Reaction of the adduct with two equivalents of KC8 in toluene at room temperature afforded the N‐heterocyclic carbene silylene‐stabilized digermanium(0) complex [L{(Me3Si)2N}Si→ GeGe←Si{N(SiMe3)2}L] (3). X‐ray crystallography and theoretical studies show conclusively that the N‐heterocyclic silylenes stabilize the singlet digermanium(0) moiety by a weak synergic donor–acceptor interaction.